The Impact of Using Smartphones on Social Interaction and PJOK Learning Outcomes in Students of SMPN 2 Jombang - Puspitaningsari, Mecca (JOURNAL RESPECS (Research Physical Education and Sports), 2023)
The aim of this research is to determine the impact of smartphone use on social interaction and PJOK learning outcomes for students at SMPN 2 Jombang. The subjects of this study were class VII students of SMPN 2 Jombang, totaling 320 students. The research design uses a correlational descriptive method with a quantitative approach. Data on smartphone use and social interaction were obtained from a questionnaire consisting of 19 statements for smartphone use and 45 statements for social interaction using a Likert scale. Meanwhile, data on PJOK learning outcomes was obtained from the final grades of the even semester for the 2023–2024 academic year for PJOK subjects. The results of the study show that the impact of smartphone use on social interaction is 5.3%; with each smartphone usage value increasing by 1 point, the social interaction value will decrease by 0.337. Meanwhile, the impact of smartphone used on PJOK learning outcomes is 18.7%; with each smartphone use value (X) increasing by 1 point, the PJOK learning outcomes (Y2) will decrease by 0.433. From these results, it can be concluded that excessive smartphone use has a negative impact on social interaction and PJOK learning outcomes.